Nursing intervention for ischemic stroke victims: an integrative review (Research, Society and Development, 2023)
Nursing care brings as attributes to the nurse the consultation and evaluation in nursing, prescription of care through interventions to be performed by the whole team, being this composed by the nursing technician and nurse. To this end, nursing care must be performed synchronously and established through institutional protocols, which reduces unnecessary interventions and failures in care. Objective: this study aims to understand the possible nursing interventions for stroke-I patients during treatment and discharge. Methodology: integrative review study with pre-established criteria. Results: it was possible to find a total of 14 full articles after using the search tool and pre-defined criteria, which answered the guiding question of this study. Conclusion: It is evident that interventions for stroke patients go beyond the emergency room, through the moment of discharge and are decisive for their reintegration into society. During emergency care, the role of nursing care is notorious, since it is the professional responsible for monitoring health status, administration of drugs such as antithrombotic agents.